Digital evidence strategies for digital forensic science examinations - Horsman, Graeme (Elsevier, 2023)
Given the size and complexity of many digital forensic science device examinations, there is a need for practitioners to formally and strategically determine a course of conduct which allows them to undertake the most robust and efficient examination possible. This work outlines both the need for practitioners to have a digital evidence strategy (DES) when tackling any given examination scenario, how to construct one and the concerns which exist when no formal DES is in place. Approaches to DES development are examined and the context to which they should be deployed are analysed, with focus being on the use of DESs at the examination/processing stage of the investigative workflow. Finally, a ‘DES skeleton’ is offered to guide practitioners as they seek to create their own DES.
Keywords: Digital Evidence; Strategy; Examination; Digital Forensics; Investigation